2015
DOI: 10.1088/1367-2630/17/4/043010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures to reveal coordinated cytoskeleton-nucleus reorganization duringin vitroinvasion of cancer cells

Abstract: Metastasis formation is a major cause of mortality in cancer patients and includes tumor cell relocation to distant organs. A metastatic cell invades through other cells and extracellular matrix by biochemical attachment and mechanical force application. Force is used to move on or through a 2-or 3-dimensional (3D) environment, respectively, or to penetrate a 2D substrate. We have previously shown that even when a gel substrate is impenetrable, metastatic breast cancer cells can still indent it by applying for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Single cells and monolayers have been shown to directly interact with the environment, changing their morphology, applying force and deforming the substrate and neighboring cells [34,35] . Specifically, the Weihs lab have shown that single cancer cells may locally deform soft elastic gels, by modifying their internal structures to facilitate force application [5,36,37] , an ability which correlates directly with their tendency to invade adjacent tissue. Mechanical interactions of cells with their substrates have also been shown to affect differentiation, alignment, and migration capabilities [38][39][40] .…”
Section: Applying and Estimating Dynamic Deformations And Responses Omentioning
confidence: 99%
“…Single cells and monolayers have been shown to directly interact with the environment, changing their morphology, applying force and deforming the substrate and neighboring cells [34,35] . Specifically, the Weihs lab have shown that single cancer cells may locally deform soft elastic gels, by modifying their internal structures to facilitate force application [5,36,37] , an ability which correlates directly with their tendency to invade adjacent tissue. Mechanical interactions of cells with their substrates have also been shown to affect differentiation, alignment, and migration capabilities [38][39][40] .…”
Section: Applying and Estimating Dynamic Deformations And Responses Omentioning
confidence: 99%
“…15,16 When cells indent, we collect 3 images: a DIC cell image, a fluorescence image of particles at the gel surface, and a fluorescence image of particles at the lowest indentation depth -the lowest focal depth where particles are observed. 15,16 When cells indent, we collect 3 images: a DIC cell image, a fluorescence image of particles at the gel surface, and a fluorescence image of particles at the lowest indentation depth -the lowest focal depth where particles are observed.…”
Section: Indentation Depth Determinationmentioning
confidence: 99%
“…Traction forces applied by cells are determined through the deformation induced to 2-dimensional (2D) or 3-dimensional (3D) compliant gels. 15,16 Many studies have been focused on the effects of stiffness or degradability of the matrix on the lineage commitment and fate of stem cells, with special focus on naïve mesenchymal stem cells (MSCs). This approach has been used, for example, to evaluate traction forces associated with fibroblast migration, 12 tumour cell migration, 13 to measure the contractility of vascular smooth muscle cells, 14 and even modified to evaluate normal forces applied by cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…They found a typical pull-push pattern, such that the cell is pulling up at the periphery and pushing down with the cell body. The upward forces might arise from actin fibres being anchored at the dorsal side of the cell or at the upper side of the nucleus, while the downward force might be the reaction force localized by the large and relatively stiff nucleus [67]. Here we include these normal forces in our simulations by adding force in the positive z-direction to our adhesion patches that are counterbalanced by an extra traction patch located at the cell centre.…”
Section: Methods Validationmentioning
confidence: 99%